A systematic review of barriers to public sector innovation process. Issue 2 (1st February 2019) - Cinar, Emre; Trott, Paul; Simms, Christopher
ABSTRACT: This article provides a systematic review of the empirical literature on barriers within public sector innovation processes, based on data from 63 articles. We investigate the nature of barriers using four dimensions: (i) classification; (ii) interrelations; (iii) innovation process and (iv) types of innovations. A new classification is developed to show that interaction-specific barriers emerge during collaborative innovation. Significantly, we identify that the nature of barriers are more complex than has previously been recognized, where there has been an emphasis on organizational barriers. We identify that the nature of barriers differ in process and innovation types. Moreover, they show interrelations across the process.